Bio- and Nanosorbents from Natural Resources - Bhardwaj Mishra, Shivani; Mishra, Ajay Kumar; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2018)
This book reviews the work in the field of nanoadsorbents derived from natural polymers, with a special emphasis on materials finding application in water remediation. It includes natural materials both with an organic or an inorganic skeleton, from which the nanomaterials can be made. Those nanomaterials can therefore be used to reinforce other matrices and in their pristine form have an extraordinary adsorption efficiency. Being of natural or biological origin, the materials described in this book distinguish themselves as eco-friendly and non-toxic.  The book describes how these benefits of the described materials can be combined and exploited. It will thus appeal to chemists, nanotechnologists, environmental engineers and generally all scientist working in the field of water pollution and remediation as an inspiration for the innovation toward new technologies. .
Biosorbents from agricultural byproducts: Updates after the 2000's -- Carbon nanoadsorbents for removal of organic contaminants from water -- Lignin and chitosan based materials for dye and metal ion remediation in aqueous systems -- Cationic nanosorbents biopolymers: Versatile materials for environmental clean-up -- Alginate based nanosorbents for water remediation -- Chitosan based natural biosorbents: Novel search for water and wastewater desalination and heavy metal detoxification -- Application of biomaterials for elimination of damaging contaminants from aqueous media -- Synthesis and application of silica nanoparticles based biohybrid sorbents.
Keywords: Polymers; Water; Hydrology; Nanotechnology; Environmental engineering; Biotechnology; Bioremediation; Microtechnology; Microelectromechanical systems; Pollution; Polymers; Water; Nanotechnology; Environmental Engineering/Biotechnology.; Microsystems and MEMS; Pollution